Archives Maintenance Management at Commission D of the Regional People's Representative Council of North Sumatra Province - Narasyah Salmehira; Juliana Nasution (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This research is about the management of archival maintenance at Commission D of the Regional People's Representative Council of North Sumatra Province, researchers want to see how the DPRD has managed archives over the past few years whether the maintenance is good or not. This study uses a qualitative approach where the results of this study were obtained by observation and interviews. and using primary and secondary data sources. The results of this study are the documents that have been archived are not in accordance with the group, for example, the 2016 letter was in the 2015 letter group, then when placing the file in the drawer, the employee did not pay attention to whether the archive/document was easily damaged or not, easily folded or folded. no. This makes the practitioner and other employees confused when looking for the document/archive again. However, the practitioner is able to overcome these obstacles by putting into practice the theory that the practitioner has obtained when the practitioner takes courses in class. So that researchers can draw the conclusion that the governance in document archiving in the DPRD North Sumatra is not good.